SHIPS for America Act의 법⋅정책적 분석을 통한 대한민국 조선⋅해운산업의 틈새전략의 재구성 - 진호현; 이창희 (Journal of Global and Area Studies , 9(1), 2025)
이 연구는 2024년 SHIPS for America Act의 입법 구조와 정책적 의의를 다층적 관점과 기회의 창 이론을 적용하여 분석하였다. 특히, 이 법안이 대한민국 조선해운산업에 미치는 정치⋅경제⋅사회⋅정책적 영향을 평가하고, 단계적 대응 전략과 틈새전략을 제시함으로써 학문적⋅정책적 기여점을 제공한다. 미국은 경제적 민족주의 기조 속에서 조선산업 국산화 및 신뢰 기반 공급망 재편을 목표로 보호주의를 강화하고 있다. 이에 따라 대한민국 조선산 해운업은 시장 경쟁 심화 및 진입 장벽 확대라는 도전과 동시에, LNG⋅수소⋅암모니아 추 진 친환경 선박, 자율운항 기술, 유지보수 및 정비 사업 등에서 새로운 시장 진출 기회를 모 색할 수 있다. 이 연구는 대한민국 조선해운산업이 신뢰 기반 회복력과 지속 가능성 확보를 위해 민관학 협력 거버넌스 구축을 제시하며, ① 민관학 협력 플랫폼 구축, ② 친환경⋅자율 운항 선박 기술 협력, ③ 선박금융 지원 및 투자 활성화, ④ 조선⋅해운 전문 인력 양성을 포함한 4단계 대응 로드맵을 단계별로 제시하였다. 그러나 이 연구는 법안 시행 이후 실증 분석, 정량적 모델링, 주요국과의 다자 협력 연구 등은 향후 보완이 필요하다. 그럼에도 이 연구는 글로벌 공급망 재편 속 대한민국 조선⋅해운산업의 전략적 방향성을 제시함으로써 새 로운 패러다임 전환에 대비하고 글로벌 시장에서 경쟁력을 강화하는 데 기여할 것으로 기대 된다. This study analyzes the legislative structure and policy significance of the 2024 SHIPS for America Act by applying the Multi-Level Perspective and Window of Opportunity theories. In particular, the study evaluates the political, economic, social, and policy impacts of this legislation on South Korea’s shipbuilding and shipping industries, while proposing phased response strategies and niche strategies, thereby contributing to both academic and policy discussions. The United States, under the banner of economic nationalism, has strengthened protectionist policies aimed at the localization of the shipbuilding industry and the restructuring of a Trusted Maritime Supply Chain. As a result, South Korea’s shipbuilding and shipping industries face the dual challenge of increased market competition and higher entry barriers, while simultaneously identifying new opportunities in markets such as LNG, hydrogen, and ammonia-powered eco-friendly vessels, autonomous navigation technology, and the Maintenance, Repair, and Overhaul sector. This study suggests that to secure resilience and sustainability based on trust, South Korea’s shipbuilding and shipping industries must establish a collaborative governance framework involving the public and private sectors, academia, and research institutions. Accordingly, the study presents a four-stage response roadmap, which includes: ① Establishment of a public-private-academic collaboration platform, ② Development of cooperation in eco-friendly and autonomous ship technologies, ③ Expansion of ship financing support and investment promotion, and ④ Enhancement of workforce training for the shipbuilding and shipping industries. However, this study acknowledges certain limitations, including the need for empirical analysis after the law’s implementation, quantitative modeling, and research on multilateral cooperation with key countries. Nevertheless, by outlining a strategic direction for South Korea’s shipbuilding and shipping industries within the global supply chain restructuring, this study is expected to contribute to preparing for a paradigm shift and strengthening competitiveness in the global market. KCI Citation Count: 0